Caries prevalence and severity in association with sociodemographic characteristics of 9-to-12-year-old school children in Al-Madinah, Saudi Arabia - Amal Aqeeli; Alla T. Alsharif; Estie Kruger; Marc Tennant; Hala Bakeer (Saudi Dental Journal)
Aim: This study was conducted to estimate the prevalence and severity of dental caries in 9-to-12-year-old schoolchildren in Al-Madinah, Saudi Arabia (SA); to compare its expression by mean of decayed, missing and filled teeth (dmft/DMFT) and the Significant Caries Index (SiC Index); to examine the association between caries experience and sociodemographic factors; and to determine whether schoolchildren in Al-Madinah are at greater risk for high levels of dental caries. Materials and methods: Data of 1,000 schoolchildren aged 9–12 years old from a cross-sectional oral health survey in Al-Madinah, SA was obtained and analysed. Dental caries was measured using dmft/DMFT and the SiC Index which was computed into two groups: highest 30% DMFT scores (SiC30) and highest 10% DMFT scores (SiC10). Sociodemographic variables included age, gender, nationality, school type (public or private) and family income. Descriptive and inferential were calculated to estimate caries prevalence and severity and its association with sociodemographic factors. Results: Caries prevalence in primary or permanent teeth was 85.1%, with untreated caries of 76.1%. The mean dmft was 2.66 ± 2.63 while the mean DMFT was 1.43 ± 1.73. Caries severity was significantly higher among males, Saudis, those from low-income families and those from public schools (p < 0.05). The mean values of SiC30 (3.52 ± 1.57) and SiC10 (4.98 ± 1.77) were considerably higher than the overall average DMFT value. Conclusion: Dental caries persists as a public health challenge among schoolchildren in Al-Madinah, SA, with a very high prevalence and severity among schoolchildren. The use of the SiC Index highlighted the subgroups with more severe caries experience.